Attack at Chosin the Chinese second offensive in Korea - Li, Xiaobing 1954- (University of Oklahoma Press, 2020)
"Explores the role of command and control, technology, and combat effectiveness from the point of view of the Chinese, and examines the cooperation and friction between Beijing and Pyongyang during the Battle of Chosin Reservoir"--
Keywords: Geschichte 1950; Schlacht um den Changjin-Stausee; China; Korean War, 1950-1953 / Campaigns / Korea (North) / Changjin Reservoir; Korean War, 1950-1953 / Participation, Chinese; Military campaigns; Korea (North) / Changjin Reservoir; 1950-1953